THREE SPECIES OF RHOMBOGNATHINE MITES (ACARI HALACARIDAE) FROM THE COAST OF RECIFE, BRAZIL - Abé, Hiroshi; Fernandes, Múcio Luiz Banja (Revista Nordestina de Zoologia, 2011)
Three species of the genus Rhombognathus (Acari: Halacaridae) are described from the coast of Recife, north-eastern Brazil, viz. Rhombognathus levigatus Bartsch 2000, R. areolatus sp. nov. and R. recifensis sp. nov. Rhombognathus levigatus was originally described from Australia. Several morphological variations between Australian and Brazilian specimens are recognized. Rhombognathus areolatus sp. nov. is similar to the Chilean species R. eltanini Newell 1984. However, R. areolatus is distinguished from R. eltanini by the protruded posterior margin of the anterior dorsal plate and the leg chaetotaxy. Rhombognathus recifensis sp. nov. resembles the Australian species R. delicatulus Bartsch 2000, however, differs from the latter mainly in leg chaetotaxy.